Victory or Defeat? Kinderland as a Battlefield of Collective Memory - Poonsombat, Waraphorn; Sintupattanapun, Weerawut (Manutsat Paritat: Journal of Humanities, 2026)
Literature has always functioned as an essential medium of collective memory, allowing historical events to be experienced more deeply than mere facts. In this context, the graphic novel, as a hybrid genre of image and text, offers a unique aesthetic dimension for conveying emotions and subjective perspectives. This study examines Mawil’s work Kinderland as a medium of collective memory. The goal is to analyze what collective memory is represented in Mawil’s Kinderland and how. Astrid Erll’s (2017) theoretical framework on the rhetoric of collective memory is used to identify the characteristics of this representation. In addition, Michael Staiger’s (2022) picture book analysis supports the investigation of the intermodal level of memory. The research results show that both the experiential memory of friendship and the monumental memory of the fall of the Berlin Wall are represented. Interestingly, there are also points of convergence where the experiential and monumental modes appear harmoniously and simultaneously, each attempting to highlight its own role. This illustrates the unstable relationship between the two modes, which alternate, merge, or dominate one another. Consequently, Kinderland proves to be not only a medium of collective memory. It is, rather, a battlefield where both forms of memory interact in diverse ways and complement each other.